Non‐invasive prenatal diagnostic testing for β‐thalassaemia using cell‐free fetal DNA and next generation sequencing. (29th December 2014) - Xiong, Li; Barrett, Angela N.; Hua, Rui; Tan, Tuan Zea; Ho, Sherry Sze Yee; Chan, Jerry K. Y.; Zhong, Mei; Choolani, Mahesh
Abstract Objective To develop an accurate non‐invasive prenatal test using next generation sequencing (NGS) for HbE and the four most common β‐thalassaemia mutations found in South East Asia (namely −28A > G, CD17A > T, CD41/42(−TTCT) and IVS‐II‐654C > T). Methods Cell‐free DNA was extracted from maternal plasma from 83 families where both parents were carriers of the HbE mutation or one of four common β‐thalassaemia mutations. Overlapping PCR amplicons covering each mutation were generated, pooled and sequenced using the Illumina MiSeq. Fastq files were analysed to detect inheritance of the paternal mutation. Results In two cases where the fathers were compound heterozygotes for HbE and −28A > G, the fetus was correctly diagnosed as having inherited one of the paternal mutations. In 35/85 cases, the paternal mutation was not detected, and in 50/85 cases, it was classified as inherited. Overall sensitivity for detection of paternal mutations was 100% (95% CI: 92.4–100%), and specificity was 92.1% (95% CI: 79.2–97.3%). Conclusion We demonstrated that detection of paternal mutations using NGS can be readily achieved with high sensitivity and specificity, removing the need for an invasive test in 50% of pregnancies at risk of a thalassaemia in cases where the father and mother carry a different mutation. © 2014 John Wiley & Sons, Ltd.